2014
DOI: 10.1016/j.nbd.2014.04.019
|View full text |Cite
|
Sign up to set email alerts
|

A study of the role of the FOXP2 and CNTNAP2 genes in persistent developmental stuttering

Abstract: A number of speech disorders including stuttering have been shown to have important genetic contributions, as indicated by high heritability estimates from twin and other studies. We studied the potential contribution to stuttering from variants in the FOXP2 gene, which have previously been associated with developmental verbal dyspraxia, and from variants in the CNTNAP2 gene, which have been associated with specific language impairment (SLI). DNA sequence analysis of these two genes in a group of 602 unrelated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 44 publications
(58 reference statements)
1
11
0
Order By: Relevance
“…Two other genes in this pathway, GNPTG and NAGPA, were reported to have an increased burden of rare nonsynonymous variants in stuttering cases from Pakistan and North America (73). The same research team followed up these genes in case-control cohorts from Brazil and North America (partially overlapping the earlier study) and again suggested an excess of rare nonsynonymous variants in cases, although no gene showed a consistent pattern in both cohorts (58). The GNPTAB variant in the original family was not fully penetrant and a substantial proportion of stutterers in that family did not carry it (high phenocopy rate).…”
Section: Exploiting Molecular Networkmentioning
confidence: 78%
See 1 more Smart Citation
“…Two other genes in this pathway, GNPTG and NAGPA, were reported to have an increased burden of rare nonsynonymous variants in stuttering cases from Pakistan and North America (73). The same research team followed up these genes in case-control cohorts from Brazil and North America (partially overlapping the earlier study) and again suggested an excess of rare nonsynonymous variants in cases, although no gene showed a consistent pattern in both cohorts (58). The GNPTAB variant in the original family was not fully penetrant and a substantial proportion of stutterers in that family did not carry it (high phenocopy rate).…”
Section: Exploiting Molecular Networkmentioning
confidence: 78%
“…These cases illustrate the diversity of genetic lesions that can (91). Targeted resequencing of FOXP2 has been performed in individuals with speech/language disorders that do not include features of CAS (58,103,137). Exome sequencing data are now also available from large cohorts of individuals with various developmental disorders (25).…”
Section: Foxp2 In Speech and Language Disordermentioning
confidence: 99%
“…The present study suggests astrocytes as a previously unsuspected site of the pathophysiology underlying human stuttering. Because Gnptab is universally expressed in brain cells and tissues (49,58,59), a current question is why astrocytes present an increased susceptibility to pathology from partial loss of function mutations in Gnptab compared to other brain cell types. We note that our data do not completely rule out the possibility that other brain cells are involved in pathogenesis of stuttering associated with mutations in Gnptab (22).…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent targeted sequencing in unrelated individuals of Asian and European descent uncovered further missense variants in GNPTAB, and in the related genes GNPTG and NAGPA (Kang et al 2010). The same research team recently reported an excess of rare coding variants in GNPTAB and NAGPA (although not in GNPTG) in an expanded sample of stuttering cases (Han et al 2014), but further independent replication studies are needed to determine the overall contribution of mutations in these genes to the etiology of developmental stuttering.…”
Section: Stutteringmentioning
confidence: 99%
“…FOXP2 has not been directly implicated in other communication disorders beyond CAS, underlining the specificity of the phenotype resulting from FOXP2 disruptions (Newbury et al 2002;Han et al 2014;Toma et al 2013). However, given that it is a transcription factor, genes regulated by FOXP2 could have roles in other forms of language disorder.…”
Section: Stutteringmentioning
confidence: 99%